Implementasi Aplikasi Berbasis Mobile menggunakan Framework React Native dan Algoritma C4.5 untuk Rekomendasi Kelayakan Penerima Bantuan Yatim Impian Indonesia - Mochammad Alvian Kosim; Setiawan Restu Aji; Muhammad Darwis (Universitas Budi Darma, 2023)
One of the programs of Yatim Impian Indonesia, a foundation that focuses on social and education, is sharing carts for MSMEs (Gedor UMKM). Cart beneficiaries are selected based on certain qualifications so that they are considered eligible. However, in its implementation, there are problems in determining the eligibility of beneficiaries quickly. One of them is that the selection criteria have not been structured. To overcome the difficulties in determining the eligibility of beneficiaries quickly, a classification model is needed. This research aims to create a cross-platform mobile application that has the function of classifying the eligibility of beneficiaries by utilizing the C4.5 decision tree algorithm. This algorithm can provide recommendations to the foundation regarding whether the beneficiary is eligible to get a cart, based on the performance of the decision tree in the C4.5 algorithm. Furthermore, the classification model obtained from the decision tree is implemented in a mobile application to meet the needs of foundation administrators who are on duty in the field in conducting surveys. Using K-Fold Cross Validation Testing, the results of the C4.5 algorithm classification model show 81% accuracy in determining the eligibility of beneficiaries, and the results of the mobile application built with the React Native Framework which have been tested with Black Box testing show that all functional parts of the mobile application have run well.